Body Temperature at the Emergency Department as a Predictor of Mortality in Patients With Bacterial Infection. Issue 21 (May 2016) - Yamamoto, Shungo; Yamazaki, Shin; Shimizu, Tsunehiro; Takeshima, Taro; Fukuma, Shingo; Yamamoto, Yosuke; Tochitani, Kentaro; Tsuchido, Yasuhiro; Shinohara, Koh; Fukuhara, Shunichi
Abstract : Abstract: Hypothermia is a risk factor for death in intensive care unit (ICU) patients with severe sepsis and septic shock. In the present study, we investigated the association between body temperature (BT) on arrival at the emergency department (ED) and mortality in patients with bacterial infection. We conducted a retrospective cohort study in consecutive ED patients over 15 years of age with bacterial infection who were admitted to an urban teaching hospital in Japan between 2010 and 2012. The main outcome measure was 30-day in-hospital mortality. Each patient was assigned to 1 of 6 categories based on BT at ED admission. We conducted multivariable logistic regression analysis to adjust for predictors of death. A total of 913 patients were enrolled in the study. The BT categories were <36, 36 to 36.9, 37 to 37.9, 38 to 38.9, 39 to 39.9, and ≥40 °C, with respective mortalities of 32.5%, 14.1%, 8.7%, 8.2%, 5.7%, and 5.3%. Multivariable analysis showed that the risk of death was significantly low in patients with BT 37 to 37.9 °C (adjusted odds ratio [AOR]: 0.2; 95% confidence interval [CI] 0.1–0.6, P = 0.003), 38–38.9 °C (AOR: 0.2; 95% CI 0.1–0.6, P = 0.002), 39–39.9 °C (AOR: 0.2; 95% CI 0.1–0.5, P = 0.001), and ≥40 °C (AOR: 0.1; 95% CI 0.02–0.4, P = 0.001), compared with hypothermic patients (BT <36 °C). The higher BT on arrival at ED, the better the outcomes observed in patients with bacterial infection were.